Optimizing Transmission Line Operation and Maintenance for Better Stability of Power Systems in Rural Areas - Yurika Yurika (Jurnal Riset Teknologi Pencegahan Pencemaran Industri, 2025)
The efficient operation and maintenance of transmission lines play a critical role in ensuring the stability of power systems, particularly in rural areas where infrastructure challenges and limited resources are prevalent. This study explores strategies for optimizing transmission line operations and maintenance to improve the overall stability and reliability of power supply in rural regions. Given the unique challenges posed by geographical remoteness, harsh environmental conditions, and financial constraints, it is essential to develop tailored approaches that enhance the performance of transmission lines while minimizing downtime and operational costs. The research employs a combination of advanced monitoring systems, predictive maintenance techniques, and localized repair strategies to address these challenges. Through data analysis and case studies from rural power systems, the study identifies key factors influencing the reliability of transmission lines, including environmental impact, maintenance scheduling, and infrastructure resilience. The findings suggest that the integration of smart grid technologies and condition-based monitoring can significantly reduce power interruptions, enhance fault detection capabilities, and optimize resource allocation for maintenance activities. Moreover, the study proposes a set of best practices for rural transmission line management, focusing on cost-effective solutions without compromising system stability. This research contributes to the development of sustainable power systems in rural areas, ensuring that power reliability is enhanced, operational costs are minimized, and long-term stability is achieved.